Swiftlet’s Nest as Potential Prebiotic Compound for the Gut Beneficial Bacteria (Jurnal Ilmu dan Teknologi Hasil Ternak, 2021)
Swiftlet’s clean and edible nest has been consumed for centuries as health food. The benefits of the edible bird nest (EBN) are commonly based on historical and observational reports since its discovery, until some were proven scientifically at recent times. The EBN has a potential to be a prebiotic with the bioavailability of glycan within the EBN. In order to test the prebiotic potential, the EBN glycoprotein and EBN extracted glycan went through a simulated human digestion in vitro test which contained at the level of oral, gastric and small intestine. The undigested components were collected and further tested with simulated in vitro human colon model. The findings showed that the improved growth of beneficial bacteria in the presence of EBN substrates have potentials to provide health benefits. The beneficial group of bacteria may improve and strengthened the host immune system and reducing the risk of pathogenic bacterial infection. These health benefits are crucial especially during the severe health situation such as the pandemic of COVID-19. This study had contributed to the functional properties of the EBN, as a prebiotic for the benefits of consumers and EBN industries. The fundamental of this finding in regards to prebiotic activity can be applied to the area of animal production in the application of prebiotics as value added animal feed ingredients.